Pembinaan Karakter Sopan Santun Anak Usia Sekolah Dasar Melalui Kegiatan Dzikir - Sukron Djazilan; Nafiah Nafiah; Pance Mariati (Indonesia Berdaya, 2024)
The objectives of community service through the character development program for elementary school aged children are: 1) To improve the polite character of elementary school aged children at the Nafisa Foundation, 2) to develop elementary school aged children at the Nafisa Foundation through regular dhikr activities. routinely, 3) Provide assistance in developing the polite character of elementary school age children at the Nafisa Foundation. The method that will be carried out in community service is to develop the religious character of elementary school age children through dhikr activities. The partner in this community service is the Nafisa Foundation, which is one of the elementary schools used as a place for the campus teaching program. The steps taken to overcome partners' problems regarding literacy and numeracy are four activities, namely pre-PKM activities, implementation of PKM activities, evaluation of PKM implementation and follow-up and improvement of community service activities.The results of the training are as follows: 1) improving the polite character of elementary school age children in terms of respecting their elders after participating in dhikr activities is clear evidence of the positive impact that religious activities such as dhikr can produce in shaping children's character. This shows the importance of integrating character education in the education system and utilizing religious activities as a tool for building strong character. 2) increasing the polite character of elementary school age children in terms of saying hello when meeting older people after participating in dhikr activities is clear evidence of the positive impact that religious activities such as dhikr can produce in shaping children's character. Several suggestions for community service results based on the conclusions that have been expressed: 1) For elementary school age children, Introduction to Values: Start with an introduction to values such as politeness, respect for elders, unselfishness, and others. Use stories or concrete examples that suit children's understanding. 2) For parents, they can be active in supporting children's dhikr activities at home. This could involve doing dhikr together, reading stories about character values, or talking about related personal experiences.Abstrak: Tujuan dari program pengabdian masyarakat yang berfokus pada pembinaan karakter anak sekolah dasar di Yayasan Nafisa adalah tiga lipat: 1) untuk meningkatkan sopan santun mereka, 2) untuk membina perkembangan melalui kegiatan dzikir (mengingat Tuhan) secara rutin, dan 3) untuk memberikan bantuan dalam menumbuhkan karakter sopan santun mereka. Metode yang digunakan dalam layanan ini melibatkan kegiatan dzikir untuk mengembangkan karakter religius anak-anak. Yayasan Nafisa, sebuah sekolah dasar dan mitra dalam layanan ini, berfungsi sebagai tempat untuk program pengajaran kampus. Program ini terdiri dari empat tahap: kegiatan pra-layanan, implementasi, evaluasi, dan tindak lanjut untuk perbaikan. Hasil dari pelatihan ini tampak dalam peningkatan sopan santun anak-anak. Rasa hormat mereka terhadap orang yang lebih tua dan kebiasaan mereka menyapa orang yang lebih tua saat bertemu telah meningkat secara signifikan setelah berpartisipasi dalam kegiatan dzikir. Perbaikan ini menunjukkan pengaruh positif dari kegiatan religius seperti dzikir dalam membentuk karakter anak-anak, sehingga menyoroti pentingnya integrasi pendidikan karakter ke dalam sistem pendidikan. Rekomendasi berdasarkan kesimpulan ini meliputi: 1) memperkenalkan nilai-nilai seperti kesopanan, hormat kepada orang yang lebih tua, dan ketidak-egoisan kepada anak-anak menggunakan cerita atau contoh yang dapat mereka mengerti; dan 2) mendorong orang tua untuk secara aktif mendukung kegiatan dzikir anak-anak mereka di rumah, yang bisa mencakup melakukan dzikir bersama, membaca cerita tentang nilai-nilai karakter, atau berbagi pengalaman pribadi yang relevan.